Research on distributed data acquisition software for high frame rate area detectors - SHANG Kunlin; LI Zhengheng; JU Xudong; ZHOU Yue; HUAI Ping; LIU Zhi (He jishu)
BackgroundThe high frame rate area detector is the core detector for the major imaging-based experimental stations at the Shanghai HIgh repetitioN rate xfel and Extreme light facility (SHINE), and its data throughput is expected to reach more than 20 GB·s-1. For the real-time receiving and processing of tens of GB·s-1 raw data, traditional single-machine systems are difficult to cope with.PurposeThis study aims to propose a multi-node distributed data acquisition and processing software architecture for high frame rate area detector at imaging-based experimental stations of SHINE.MethodsFirstly, the performance of different network libraries was investigated, and the synchronous transmission method combined with CPU thread binding was found to have the best single-thread data receiving performance. Then, a parallel event building method was introduced by simultaneously dispatching and combing different module data across multiple nodes based on Bunch ID. Furthermore, the data calibration and the bitshuffle/LZ4 compression algorithm were implemented and tested.ResultsTest results show that the highest single-thread data receiving rate is achieved at nearly 3 GB·s-1, a parallel event building data rate of approximately 23.5 GB·s-1 is achieved by using 4 server nodes, and the realized compression ratio is about 5.7.ConclusionsThe feasibility of the multi-node distributed parallel data acquisition method for high frame rate area detector is verified in this study, providing a foundation for the subsequent development of high-throughput data acquisition software for area detectors.